CONDIŢII CLIMATICE FAVORABILE ŞI RESTRICTIVE PENTRU CULTURA PLANTELOR ÎN DEPRESIUNEA ALBA IULIA - TURDA (PANGEEA, 2025)
Favorable and restrictive climatic conditions for culture of plants in Alba Iulia - Turda Bazin. The present study describes the climatic conditions that have a major influence on the cultivation of plants, a traditional occupation in this part of the Transylvanian Depression. The favourable climate, reflected in the variables of temperature, precipitation, soil freeze, hoar frost, snow and snow layer, is occasionally associated with extreme events. The paper discusses also their adverse effects on crops.